Research, innovation and technological performance in Germany - EFI Report 2010 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2010)
In this third report, the following five topics are addressed in detail. First, the Expert Commission analyses the overall structure of the German innovation system and in particular the role of non-university research (Section B 1). It then presents an interim assessment of the Bologna Process, which is currently the subject of lively public debate (Section B 2). Twenty years after German reunification, research and innovation policies in eastern Germany are reviewed (Section B 3). The Expert Commission also considers Germany's technological performance in the field of electromobility (Section B 4), and comments on the efforts of the European Commission to introduce a European Union patent and a unified patent court system (Section B 5). Highest priorities for the Federal Government should be the introduction of R&D tax support, improvements to the conditions for Business Angels and venture capital, and the systematic improvement of Germany's education and research systems. Broad tax advantages for companies and individual tax-payers are no substitute for these urgently needed measures. Instruments which have been shown to have failed, such as the research premium, should be abandoned. Germany continues to do well in terms of creativity, inventiveness and openness to innovations. Despite financial constraints it is important to target investments in order to maintain and expand these strengths. – – In diesem dritten Gutachten werden die folgenden fünf Themenschwerpunkte ausführlich behandelt. Die Expertenkommission analysiert die Gesamtstruktur des deutschen Innovationssystems und dabei insbesondere die Rolle der außeruniversitären Forschung (Kapitel B 1). Sie stellt eine Zwischenbilanz der Bologna-Reform vor, die derzeit in der Öffentlichkeit kontrovers diskutiert wird (Kapitel B 2). 20 Jahre nach der Wiedervereinigung zieht sie ein Resümee der Forschungs- und Innovationspolitik in Ostdeutschland (Kapitel B 3). Die Expertenkommission setzt sich zudem kritisch mit der technologischen Leistungsfähigkeit Deutschlands im Bereich der Elektromobilität auseinander (Kapitel B 4) und kommentiert die Bemühungen der Europäischen Kommission um die Einführung des Gemeinschaftspatents und einer vereinheitlichten europäischen Patentgerichtsbarkeit (Kapitel B 5). Für die Bundesregierung sollten die Einführung der steuerlichen FuE-Förderung, die Verbesserung der Rahmenbedingungen für Business Angels und Wagniskapital und die systematische Arbeit an Verbesserungen des deutschen Bildungs- und Forschungssystems höchste Priorität haben. Generelle steuerliche Vergünstigungen für Unternehmen und Bürger sind kein Ersatz für diese dringend benötigten Maßnahmen. Nachweislich erfolglose Instrumente wie die Forschungsprämie sollten eingestellt werden. Hinsichtlich Kreativität, Erfindergeist und Innovationsbereitschaft schneidet Deutschland weiterhin gut ab. Trotz finanzieller Engpässe muss nun gezielt in den Erhalt und Ausbau dieser Stärken investiert werden.
Keywords: 330; Innovation; Forschung; Technischer Fortschritt; Deutschland